PENATALAKSANAAN FISIOTERAPI PADA KASUS OSTEOARTHRITIS GENUSINISTRA DENGAN MODALITASTRANSCUTANEUS ELECTRICAL NERVE STIMULATION, ULTRASOUND, DAN TERAPI LATIHAN DI RSUD KOTA BANDUNG - Caessario Stephan; Abdul Qudus; Ika Rahman (INFOKES (Informasi Kesehatan), 2023)
Background: Osteoarthritis is a chronic joint disease characterized by abnormalities in cartilage (cartilage), where abnormalities in the cartilage cause the bones to rub against each other resulting in stiffness, pain, limited movement, and disruption of daily activities. Objective: To determine the implementation of Physiotherapy in reducing pain, increasing muscle strength, increasing the scope of joint motion, and increasing functional abilities in cases of Osteoarthritihis Genu Sinistra by using tens modalities, ultrasound and exercise therapy. Results: After 6 times of therapy, the results of pain assessment in the left knee from silent pain T1 = 7 to T6 = 4 motion pain T1 = 8 to T6 = 4 tenderness T1 = 4 to T6 = 2. Increased muscle strength of knee extensors T1 = 3 to T6 = 4 and knee flexors T1 = 3 to T6 = 4. As well as an increase in the scope of motion of the passive left knee joint, namely T1 = S 00-00-1200 to T6 = S 00-00-1300 and the scope of motion of the active left knee joint, namely T1 = S 00-00-1000 to T6 = S 00-00-1200. Conclusion: Ultrasound can help reduce pain, Tens can relax the muscles, and Exercise therapy can increase muscle strength, increase the joint motion, and can improve functional abilities. Keywords: Physiotherapy, Osteoarthritis Genu, Tens, Ultrasound, Exercise therapy.